Towards an autonomous RIRS: design, structure investigation and framework - Rahman, Miftahur; Liu, Haochen; Durazo-Cardenas, Isidro; Starr, Andrew; Hall, Amanda; Anderson, Robert (IEEE, 2021)
Automated robots have been deeply embedded in many industries for decades. Autonomous railway maintenance is attracting more attention, but few robotic technologies are used in rolling stock inspection and repair. Due to geometrical differences between rail and road, wheeled robots still need to fulfill research and deployment gaps for application in railway track maintenance. This research is intended to design an autonomous Robotic Inspection and Repair System (RIRS) for unmanned track maintenance. It mainly employs commercial Warthog Unmanned Ground Vehicle (UGV), Universal Robot (e.g., UR10e) manipulator, and multiple onboard sensors to achieve navigation to track, road-rail conversion, and on-track inspection and repair. With the support of a trolley, RIRS will achieve the ability to operate both on-track and off-track. This research also investigates the system structure of the on-track inspection and repair by considering the dynamic degree-of-freedom of both UGV wheels and the joints of robot manipulator. The redundancy of joints for the mobile manipulator has been reduced by proposing simplified joints which will improve the performance and efficiency. This research analyses the dynamic principles of a new maintenance system that will be deployed and tested in a prototype RIRS system in future work.
Keywords: road rail vehicle; rail inspection and repair system; UGV; manipulator; autonomous